Assessing acellular scaffold viability with T2-weighted relaxation time value imaging: imaging variables and early clinical associations at 6 months following patellofemoral cartilage repair - Zachariah Gene Wing Ow; Dean Wang; Edmund Jia Xi Zhang; Hamid Rahmatullah Bin Abd Razak; Steven Bak Siew Wong; Jamie Xiu Mei Ho; Keng Lin Wong (Elsevier, 2024)
ABSTRACT: This study aims to describe novel magnetic resonance imaging (MRI) imaging characteristics using T2-weighted relaxation time values (T2RVs) for evaluating acellular graft status following cartilage repair, addressing the limitations identified in current imaging techniques. Nine patients (11 lesions) underwent cartilage repair procedures for patellofemoral cartilage lesions. Visual Analog Scales for pain and Tegner scores for function were the primary clinical outcomes measures, with clinical failure defined as nil improvement of either score at follow-up. Radiological outcomes were MRI variables centered around evaluating 2 main domains-graft viability and integration, with individual imaging characteristics being identified based on these 2 domains. At 6 postoperative months, clinical success was observed in 89% (8) of the patients. On average, Visual Analog Scales decreased by 2.6 and Tegner improved by 1.9 points, respectively, with just 1 patient experiencing no pain relief or functional improvement at follow-up. To evaluate the viability and integration of the implanted grafts, several pertinent magnetic resonance variables were utilized, namely T2RV distribution and range, graft surface, matrix and edge characteristics, as well as subchondral bone characteristics. The singular graft failure identified on MRI displayed unique characteristics not identified on the other grafts-that of heterogeneously high T2RV signals within the graft with a discontinuous matrix. T2RV imaging offers a noninvasive method for evaluating cartilage graft viability and integration, potentially improving postoperative monitoring and patient outcomes. Despite promising results, limitations such as sample size and lack of long-term follow-up data need to be addressed in future studies.